Metode Penentuan Faktor-faktor Keberhasilan Penting dalam Analisis SWOT - Mohamad Harisudin Mahfud (AGRISAINTIFIKA: Jurnal Ilmu-Ilmu Pertanian, 2019)
Abstract : Discussion about the strategy has become an interesting topic to be discussed. Practitioners and academics mutually support the development of strategic management. SWOT analysis is an analytical tool most widely used amongst other analytical tools.The initial stages should researchers do is set an important success factor, because the key success factors is a prerequisite to the formulation of strategic alternatives. However in the study of the meta-analysis found a fact that the existing strategy formulation has the weakness of the methodology. Among the weakness is the low level of reliability and validity of the critical success factors (strengths, weaknesses, opportunities and threats) that are set. This article proposed a solution in the form of formulation procedures critical success factors that can be replicated by other researchers as well as ease of corrective action if found errors in the determination of critical success factors. Keywords: Strategy, Critical Success Factors, Methodological, SWOT